Singapore’s Foreign Policy: A Book Review - Hardi Alunaza SD (Indonesian Perspective, 2018)
This book contains five chapter with a specific explain and contribution in every chapter. The first chapter is about Singapore’s foreign policy and explains about exceptional state. The second chapter is talking about the battle of sovereignty. The third is about transcending regional locale. The fourth explaining about Singapore and the power, and the last is about driving and suffering the region. The Island Republic of Singapore is the smallest state within South-East Asia and, indeed, within a wider East Asia. It also lacks natural resources, except for the human variety in limited numbers, and a harbor in an ideal location for servicing regional trade. In 1999, for the third year running, the Swiss based world economic forum ranked Singapore first among over fifty leading economies in its annual global competitiveness report. In its material accomplishments and attendant external recognition, Singapore is exceptional not only within its regional locale, but also globally among so called small states. The point has been well made that economic success is the main reason for Singapore’s high status and disproportionate influence in international affairs.Keywords: Singapore's foreign policy, sovereignty, small states